Subjective life satisfaction among urban Malay civil servants in Malaysia: a qualitative study - Md. Noon, Hazizan; Mohamed Harith, Nor Hafizah (2012)
Quality of life (QOL) has two main dimensions: objective and subjective. Both dimensions are equally important in determining the overall quality of life of a person (Mahadzirah et al., 2008). Hence, a comprehensive measure of people’s life satisfaction should ideally take into account these two dimensions. Empirical data for the measure of quality of life in Malaysia however has largely employed objective indicators (MQLI, 2004) and were used mainly in quantitative research. This situation has left research on subjective life satisfaction or well-being largely unexplored or limited. In light of the above, one may ask: if the MQLI has shown high score on the objective indicators, how far does this score reflect upon the people’s subjective life satisfaction. This study thus focuses on exploring subjective life satisfaction among urban Malay civil servants in Malaysia. Being qualitative in nature, the research is concerned mainly with the emic than the etic views and perspectives (Merriam, 2009). Framed withing a modified Allardt’s model of welfare and MQLI, the study explores the subjective meaning of life satisfaction among the staff members of a Malaysian public university namely Universiti Teknologi MARA or UiTM. Sixteen respondents from four different categories of the University’s administrative staff working at its main campus in Shah Alam, Selangor were engaged in the research. Data collected via in-depth interviews were later verified through written feedback validation (WFV) form. Preliminary findings have shown that the responses centered around two main themes namely satisfying non-living needs and satisfying the living needs with the former being the main priority of the respondents. These findings have significant bearing upon development policy in Malaysia.